Początki prasy periodycznej w Wilnie - Jakubenas, Regina (Kalbotyra, 1997)
The article is devoted to the history of the periodical editions in the Grand Duchy of Lithuania. It analyses the newspaper Gazeta Wilenska and particularly the publications devoted to the dissemination of ideas of the Enlightenment and the struggle against prejudice. Special attention is paid to announcements which provide us with the necessary information connected with these questions.